Relations between vitality and crime in the urban macroscale - Lima, Willian Carlos Siqueira; Verfe, Fernanda Jessie Podolak; Hardt, Letícia Peret Antunes; Hardt, Carlos; Hardt, Marlos; Pellizzaro, Patrícia Costa (International Journal of Advanced Engineering Research and Science, 2022)
Faced with the problem of non-vitalized environments that are promoters of insecurity in cities, the research aims to contribute to the field of studies on interfaces of conditions of morphology and vitality from their interactions with crimes in public spaces. In this context, its general objective is to analyze the relationship between the results of spatial syntax, obtained with the software DephtmapX, and the occurrence of crimes in these places, adopting, as a macroscale case study locus, the neighborhood Cidade Industrial de Curitiba (CIC), Brazil, which has high rates of violence. To achieve these goals, the work was divided into four main sections: theoretical foundations, related to the structuring themes of research; methodological procedures, referring to techniques and methods employed; analytical results, related to empirical interpretation in two parts (spatialization of crime spots and application of spatial syntax) and critical discussions, pertinent to the joint analysis of scientific findings. Clear interconnection of road integration with the criminal occurrence is diagnosed, with a predominance of thefts, which use precisely areas of greater quantities and densification of users. For the connectivity of pathways, the clipping and conformation of the urbanized tissue of the studied region do not allow the establishment of effective reciprocity between attributes examined. It is concluded, therefore, by the achievement of the stated objective, even if future investigations should address in more detail the connection variable and others provided by the syntactic construction of spaces in this broad scalar approach of the contemporary city.